2021
DOI: 10.5737/23688076313298305
|View full text |Cite
|
Sign up to set email alerts
|

The relationships of unmet needs with quality of life and characteristics of Indonesian gynecologic cancer survivors

Abstract: Gynecologic cancer survivors’ complex needs are too often overlooked. This study aimed to identify the associations between unmet needs and quality of life, and selected characteristics of Indonesian gynecologic cancer survivors. This study was a cross-sectional, correlation study. A total of 298 participants completed the Cancer Survivor Unmet Needs (CaSUN), EORTC QLQ-C30, and demographic and clinical-related questionnaires. A higher level of unmet needs was linked to lower perceived quality of life. Higher l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 37 publications
(48 reference statements)
1
11
0
2
Order By: Relevance
“…The themes identified were consistent with a quantitative study conducted among breast cancer patients in Malaysia, which reported that they had the highest unmet supportive care needs in the psychological domain, followed by physical, patient care needs, and health information [ 18 ]. Studies have found that unmet needs in the early postdiagnosis stage of cancer negatively impact a patient's QoL [ 7 , 19 ]. Hence, it is crucial to recognise these needs and provide sufficient supportive care right from the beginning of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The themes identified were consistent with a quantitative study conducted among breast cancer patients in Malaysia, which reported that they had the highest unmet supportive care needs in the psychological domain, followed by physical, patient care needs, and health information [ 18 ]. Studies have found that unmet needs in the early postdiagnosis stage of cancer negatively impact a patient's QoL [ 7 , 19 ]. Hence, it is crucial to recognise these needs and provide sufficient supportive care right from the beginning of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Si estas necesidades no se satisfacen, se conoce como "necesidades insatisfechas", lo que afectará la calidad de vida del sobreviviente (14,15) . Cuantas más necesidades no satisfechas, peor será la calidad de vida de las sobrevivientes de cáncer ginecológico (6,(16)(17)(18) . Por lo tanto, para mejorar la calidad de vida de los sobrevivientes, una forma a seguir es minimizar las necesidades insatisfechas (9,13,16,17) .…”
Section: Introductionunclassified
“…In 2016, the first translations of the CaSUN were completed in Dutch and Chinese [ 20 , 21 ]. To date, the CaSUN was translated into Spanish [ 22 ], Japanese [ 19 ], and Korean [ 23 ] and has been used for cancer survivors living between 6 months and up to 15 years after the end of the treatment [ 24 26 ] with a diagnosis of breast [ 21 , 27 – 29 ], colorectal [ 26 , 30 , 31 ], testicular [ 25 ], prostate [ 32 ], head and neck [ 33 ], non-small cell lung [ 23 ], gynaecologic [ 34 , 35 ], endometrial [ 36 ], and a cohort of mixed cancer types [ 12 , 19 , 20 , 24 , 37 39 ].…”
Section: Introductionmentioning
confidence: 99%